PENGRUWATAN DALAM KALATATTWA - Ni Made Ari Dwijayanthi (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
The Balinese tradition of meruwat is equated by restoring the state of objects, living things, or human beings. In addition to restore them, it means being free from all dirt, fatigue, or the like. Sometimes pengruwatan is believed to be a definition to get a better life, of course, through rituals that are carried out and believed in. Kalatattwa contains a narration that is narrated from the birth of Bhatara Kala to the gift he received from Lord Shiva. Wayang Sapuh Leger became a manifestation of religious ceremonies (rites) to emphasize the ritual. Palmer's hermeneutic theory is used to interpret the Kalatattwa, which emphasizes the rites of healing and Sapuh Leger.